An extensively validated whole-cell biosensor for specific, sensitive and high-throughput detection of antibacterial inhibitors targeting cell-wall biosynthesis - Galarion, Luiza H; Mitchell, Jennifer K; Randall, Christopher P; O’Neill, Alex J (Journal of antimicrobial chemotherapy, 2023)
Abstract Background Whole-cell biosensor strains are powerful tools for antibacterial drug discovery, in principle allowing the identification of inhibitors acting on specific, high-value target pathways. Whilst a variety of biosensors have been described for detecting cell-wall biosynthesis inhibitors (CWBIs), these strains typically lack specificity and/or sensitivity, and have for the most part not been rigorously evaluated as primary screening tools. Here, we describe several Staphylococcus aureus CWBI biosensors and show that specific and sensitive biosensor-based discovery of CWBIs is achievable. Methods Biosensors comprised lacZ reporter fusions with S. aureus promoters (PgltB, PilvD, PmurZ, PoppB, PORF2768, PsgtB) that are subject to up-regulation following inhibition of cell-wall biosynthesis. Induction of biosensors was detected by measuring expression of β-galactosidase using fluorogenic or luminogenic substrates. Results Three of the six biosensors tested (those based on PgltB, PmurZ, PsgtB) exhibited apparently specific induction of β-galactosidase expression in the presence of CWBIs. Further validation of one of these (PmurZ) using an extensive array of positive and negative control compounds and conditional mutants established that it responded appropriately and uniquely to inhibition of cell-wall biosynthesis. Using this biosensor, we established, validated and deployed a high-throughput assay that identified a potentially novel CWBI from a screen of >9000 natural product extracts. Conclusions Our extensively validated PmurZ biosensor strain offers specific and sensitive detection of CWBIs, and is well-suited for high-throughput screening; it therefore represents a valuable tool for antibacterial drug discovery.